Congressional Voting on Religious Issues: The Case of the Religious Liberty Protection Act of 1999 - Hamerly, Ivy (A journal of church and state, 2009)
Several studies have examined the influence of religious factors on congressional voting in a variety of policy areas.1 Few opportunities have presented themsel